Tetrakis(4-cyanopyridine)palladium(II) bis(trifluoromethanesulfonate) - Adrian, R.A.; Gonzalez, D.M.; Tiekink, E.R.T.; Walmsley, J.A. (International Union of Crystallography, 2010)
The title salt, [Pd(C(6)H(4)N(2))(4)](CF(3)SO(3))(2), comprises Pd(4-cyanopyridine)(4) dications balanced by two trifluoromethanesulfonate anions. The PdII atom lies in a square-planar geometry defined by four N atoms which form equivalent Pd-N interactions. The 4-cyanopyridine ligands are twisted out of the N(4) plane, forming dihedral angles ranging from 66.5 (2) to 89.9 (2)degrees. In the crystal packing, columns of edge-to-edge dications define channels in which reside the anions. A range of C-H...N and C-H...O hydrogen-bonding interactions stabilizes the crystal packing.